Factors affecting expenditure and income of small fisherman households: Evidence from Jember, Indonesia - Sujarwo, Sujarwo; Maulidah, Afsah Indah; Setiawan, Budi (Publisher of Widyagama University of Malang (UWG Press), 2022)
Small-scale fishermen from Watu Ulo, Jember, Indonesia use very simple fishing gear and small boats use nets. Thus, they receive a low catch and affect their well-being. This study aims to analyze the factors that can affect the income and expenditure of fishers’ households. This study interviewed fishermen in Watu Ulo Hamlet, Ambulu District, using simple random sampling. The analytical method in this study used the Two-stage Least Square (2SLS) method to estimate the parameters of the equation. The results showed that the fishing income was influenced by the selling price of the fish and fishing production. Non-fishing income was influenced by total household income and fishermen's education. Husband's work at sea did not affect non-fishing income. Meanwhile, there were two factors that affected fishermen's household expenditures. Food expenditure was influenced by total household income, number of family members, and rice expenditure. Moreover, non-food expenditure was influenced by total household income, the number of schoolchildren, and customs. This study suggests that fishermen need to diversify their income sources into processed goods so that they can be sold in markets or shops. Such effort can increase the income of fisherman households.JEL Classification E31; J43; O11